INFLASI INDONESIA SEJAK PENERAPAN INFLATION TARGETING FRAMEWORK (ITF) TAHUN 2005 DAN FAKTOR-FAKTOR YANG MEMPENGARUHI - Ilham Tri Murdo; Redy Herinanto Albertus; Ch. Dini Ika Handayani; Mahyudin Usman (Bajang Institute, 2025)
This research is to find out the extent to which independent variable factors (GDP, Total Unag Circulating (JUB), Exchange Rate and Interest Rates) influence the dependent variable (Inflation) in the last 20 years since the implementation of the inflation targeting framework (ITF) by Bank Indonesia . Quantitative research aims to obtain empirical evidence regarding the influence of the variables GDP, Money Supply (JUB), Exchange Rate and Interest Rates on Exports, and also test hypotheses to strengthen or even reject the hypothesis. With the following results: Gross Domestic Product (GDP) has the opposite relationship and has no effect on Inflation, Money Supply has a positive and significant effect on Inflation. The exchange rate has an inverse relationship and has no effect on inflation. Interest rates have an inverse, influential and significant relationship to inflation. Gross Domestic Product (GDP), money supply (JUB), exchange rate and interest rates together (simultaneously) have a significant and significant influence on inflation